Dynamic relationship between precious metals and Central European stock markets - Siemaszkiewicz, Karolina (Dynamiczna relacja między metalami szlachetnymi i rynkami giełdowymi krajów Europy Środkowej, 2020)
High volatility and the contagion effect have led investors to consider alternative instruments as a part of their portfolios to be able to diversify away from the increasing risk in the stock markets. As alternative instruments, one can consider investing in such metals as gold, silver, copper, and platinum. This paper investigates the dynamic relationship between gold, silver, platinum, copper, and the Central European stock markets. The aim of this article is to identify if those metals can be considered as safe haven instruments for investors from the Czech Republic, Hungary, Poland, and Slovakia. The considered period is from 01.01.2007 to 30.06.2020. The calculations of DCC-GARCH model parameters were made by using the professional program OxMetrics by J.A. Doornik. There were 22 metal/metal or metal/index DCC-GARCH realization carried out. Significant differences exist in the correlation structure for two groups of metals. Gold and silver can be considered as an investment asset. Platinum and copper are mainly industrial metals. From this research, one can define silver as a safe haven instrument. During the financial crises, one can also observe the negative values of correlations between gold and indices, which means that gold served as a safe haven
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 12, s. 101-112